Successful conservative treatment of spontaneous intrathoracic esophageal perforation using a temporary covered esophageal stent with a check valve: a case report - Ryu Matsumoto; Ken Sasaki; Itaru Omoto; Masahiro Noda; Yasuto Uchikado; Takaaki Arigami; Yoshiaki Kita; Shinichiro Mori; Kosei Maemura; Shoji Natsugoe (Surgical Case Reports, 2019)
Abstract Background Spontaneous esophageal perforation is a potentially life-threatening condition with high morbidity and mortality rates. While surgical treatment has been employed for esophageal perforation, we have adopted conservative treatment with an esophageal stent for patients in a poor physical condition because we consider controlling sepsis and improving the physical status are the highest priorities; additionally, the surgical trauma could be fatal for these patients. Case presentation A 60-year-old male complaining of left chest and back pain after vomiting was transferred to a local hospital. Computed tomography and chest X-ray examinations showed left tension pneumothorax, pneumomediastinum, and bilateral pleural effusion suspicious of spontaneous intrathoracic esophageal perforation. He was transferred to our hospital for further treatment. After arrival, he developed septic shock with acute respiratory failure. We considered that surgical treatment was too invasive and chose conservative treatment with an esophageal stent. Under general anesthesia, we first inserted a 20-Fr. trocar in the left posterior pleural space, and a large volume of the dark pleural effusion was discharged. We then performed endoscopy and found a pinhole perforation in the left posterolateral wall of the lower esophagus. We inserted both a silicon-covered esophageal stent with a check valve and a double elemental diet (W-ED) tube. We then inserted an 18-Fr. trocar into the left anterior wall. These procedures were performed less than 24 h after onset. As intensive medical care, the patient was administered broad-spectrum antibiotics and catecholamine. The two trocars and the W-ED tube were under continuous suction at − 5 cmH2O and at − 20 cmH2O every 30 s. On the 6th day, we inserted an additional thoracic drainage tube into the left pleura under CT guidance. The patient was discharged from the ICU to the general ward on the 7th day. We removed the stent almost triweekly, and the esophageal perforation was completely healed on the 45th day. He was discharged home on the 70th day. Conclusion Conservative treatment with a temporary self-expanding covered stent with a check valve, sufficient drainage, and W-ED tube nutrition was useful and effective in this unstable case of spontaneous intrathoracic esophageal perforation.